Performance of Village-Owned Moro Berkah's Employees: Analyzing Workplace Motivation and Workplace Discipline - Turmudhi, Anis; Ristianawati, Yuyun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2023)
The goal of this study is to find out how employees at Moro Berkah Village-Owned Enterprise in Mororejo village, Kaliwungu district, Kendal Regency, Central Java, Indonesia, perform when motivated and disciplined at work. The unprofessional performance of employees at Moro Berkah Village-Owned Enterprise serves as the background. The independent variables in this study are work motivation and work discipline. Quantitative research is the focus of this kind of study. In order to collect data, questionnaires were distributed to forty employees. Multiple linear regression analysis was used for the data analysis. Work discipline and work motivation were found to have positive and significant effects on employee performance, according to the findings.